2019
DOI: 10.4314/jasem.v22i12.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage on borehole water quality stored in plastic containers for prolong periods

Abstract: Water may become contaminated at any point between collection, storage and usage. This study examined the effects of storage on borehole water quality stored in plastic containers for prolong periods. Three brands of plastic containers filled with borehole water were collected from homes in Ugbowo, Benin city. Physicochemical parameters were determined using standard methods. Total bacterial and coliform counts were determined using the pour plate technique. Conductivity, TDS, Chloride, Sulphate and Nitrate we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Other authors have also observed drinking water standards within WHO maximum permissible limit (Dhanaji et al 2016;Atuanya et al 2018) For example, the highest pH recorded in the study which was from residential area (5.58 ± 0.17) was within WHO pH limit of 6.5 -8.5. Atuanya et al (2018) similarly reported pH values of 5.6 -6.6 in stored borehole water in Benin City. It has been reported that pH values of 6.5-8.0 is good for water intended for consumption (Abdullahi et al (2013).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Other authors have also observed drinking water standards within WHO maximum permissible limit (Dhanaji et al 2016;Atuanya et al 2018) For example, the highest pH recorded in the study which was from residential area (5.58 ± 0.17) was within WHO pH limit of 6.5 -8.5. Atuanya et al (2018) similarly reported pH values of 5.6 -6.6 in stored borehole water in Benin City. It has been reported that pH values of 6.5-8.0 is good for water intended for consumption (Abdullahi et al (2013).…”
Section: Discussionsupporting
confidence: 58%
“…This could be as a result of silt, organic matter and sewage gaining access to the underground water (Ukpong and Okon, 2013;Palamuleni and Akoth, 2015). Other authors have also observed drinking water standards within WHO maximum permissible limit (Dhanaji et al 2016;Atuanya et al 2018) For example, the highest pH recorded in the study which was from residential area (5.58 ± 0.17) was within WHO pH limit of 6.5 -8.5. Atuanya et al (2018) similarly reported pH values of 5.6 -6.6 in stored borehole water in Benin City.…”
Section: Discussionmentioning
confidence: 60%